Analysis and design of reset control systems - Guo, Yuqian; Xie, Lihua; Wang, Youyi (London, United Kingdom The Institution of Engineering and Technology, 2015)
The following topics are dealt with: reset control systems design; reset control systems analysis; reset control systems stability; discrete-time reset conditions and conic jump sets.
Electronic reproduction.
Keywords: Nonlinear control theory; Linear time invariant systems; Feedback control systems -- Design and construction; Control theory; Discrete-time systems; Stability; Electronic books